Synthesis of Cellulose Ether from Alkoxylyted Epoxide Methyl Esters Fatty Acids Rubber Seed Oil with Cellulose - Ginting, Adil; Keliat, Rayzki Ananta (Talenta Publisher, 2023)
The alkoxylation reaction was carried out between the fatty acid methyl ester epoxide of rubber seed oil (RSO) and cellulose to produce cellulose ether. RSO was obtained from rubber seed by extraction method with n-hexane solvent followed by a purification process including a degumming stage, bleaching and neutralization. The RSO obtained was further dimetanolized with a NaOH catalyst producing a fatty acid methyl ester which is then epoxidized with a performance acid to give the epoxide compound. The resulting epoxide compound was reacted with cellulose in an isopropanol solvent, producing ether cellulose. RSO obtained as much as 46.75% with a free fatty acid content of 0,2184%, iodine amount, and unsaturated fatty acid content of 82,4%. The resulting ether cellulose was found to be vibrations in the area waves number of (á¿¡) = 1118 cm-1, which indicates the presence of C-O-C bonds from the ether, which can indicate that an etherification reaction has occurred in cellulose. This is also supported by the presence of vibrations at wave numbers (á¿¡) = 1743 cm-1, (á¿¡) = 1165 cm-1, (á¿¡) = 1118 cm-1, (á¿¡) = 725 cm-1, each of which shows the existence of a bond (C = O) from the ester, CH3 bond, C â€“ O bond from the ester and bond to carbon (CH2) n where n â‰¥ 4, which is not found in cellulose but is found in cellulose ether. It shows that an alkoxylation epoxide reaction of MEAL rubber seed oil with cellulose has occurred, which will produce cellulose ether.